TRENDS AND APPLICATIONS OF BIG DATA IN EDUCATION (Pakistan Journal of Science, 2023)
Big data technologies have facilitated innovation across various industries, including healthcare, technology, and education. The utilization of this innovation is now required within the education sector at all levels. It is a progressing framework named as "Education 4.0" to accommodate the numerous needs of this sector. Specifically, this article first describes the architecture of big data and its properties compatible to Education sector . The process of utilizing large educational data and data mining techniques in education are explained. To find solutions to diverse educational problems, an ever-increasing variety of mining tools have been assembled. This study also provides insights into these techniques and other data sources for gathering educational data. Several applications have been developed to promote the use of big data techniques in higher education and highlight its benefits for the sector, but there are still a number of issues that need to be considered. We will highlight the obstacles of using big data techniques in higher education
Keywords: V’s; Big Data; Higher Educational Data; BDA; ERP; LMS; Data Masking